EXPERIENCE OF USE OF MODERN THERAPEUTIC METHODS OF ISCHEMIC STROKE IN THE REGIONAL CENTER OF CEREBROVASCULAR DISEASE №2 IN NOVOKUZNETSK - Волкова, Александра Константиновна; Полукарова, Елена Алексеевна; Пеганова, Марина Анатольевна; Зиборова, Светлана Станиславовна (Medicine in Kuzbass, 2022)
Objective – demonstration of the effective using of modern techniques in the treatment of ischemic stroke by the work of the regional center of cerebrovascular disease in Novokuznetsk. Methods. There is an analysis of the use of intravenous thrombolytic therapy and thromboextraction in patients with verified ischemic stroke. Thrombolytic therapy was carried out with «Actilyse». The dose was calculated of 0.9 mg per 1 kg of patient’s weight. Thromboextraction was performed using stent retrievers «Solitaire» or suction system «Penumbra». Results. For the period from 2011 to 2021, there were performed 445 procedures of intravenous thrombolytic therapy at the regional center of cerebrovascular disease N 2. The proportion of patients with TLT procedure ranges from 10.1 % to 12.3 % in different years. The severity of neurological deficit according to the NIHSS scale before the IV TLT procedure averaged 15.6 ± 7.3 points, and at discharge it was 8.1 ± 6.4 points. It was possible to reduce the mortality rate among patients undergoing TLT from 15.5 % to 4.5 % due to more careful selection of patients in recent years. Also in 2019 the procedure of mechanical recanalization (thrombextraction) was performed in 15 patients, 2020 – 17 patients, 2021 – 8 patients. The use of this method made it possible to reduce the severity of neurological deficit from an average of 18.1 ± 6.3 points to 6.5 ± 4.2 points. Conclusions. When used in practical medicine, TLT and TE have shown high efficiency in the treatment of stroke. The growth in the use of these techniques is due to a number of reasons: 1) transportation of the patient to the nearest vascular center for specialized care; 2) the arrival of young specialists who are ready to apply modern methods of treatment to the department; 3) close cooperation with ambulance workers; 4) use of a special telephone connection from the patient’s bed; 5) continuity in the work of medical services – laboratory, radiation, endovascular surgery, neurosurgery; 6) raising awareness of the population about the symptoms of stroke.